Early diabetes screening in pregnancy. Issue 1 (2nd April 2018) - Shinar, Shiri; Berger, Howard
Abstract: The present literature review was conducted to evaluate early diabetes screening in pregnancy. The review focuses on the various guidelines for early screening, the target populations for screening, and the assessment of various early screening targets and strategies. The advantages and disadvantages of each screening method are highlighted. The review emphasizes that there are no validated criteria for selecting high‐risk pregnant women for early screening. The different early screening modalities, including fasting plasma glucose, random plasma glucose, postload glucose, and hemoglobin A1c, lack concordance and have not been validated for the early diagnosis of diabetes in pregnancy. Moreover, the benefit of early screening by earlier initiation of treatment has not been shown. Until a randomized controlled trial demonstrates benefit to screening and validates a particular screening method, it is not possible to provide evidence to support any single strategy for early diabetes screening in pregnancy. Abstract : Early diabetes screening in pregnancy is commonly recommended in clinical guidelines but supporting evidence is lacking, making it difficult to recommend any single screening strategy.